Energy-efficient microwave heating for rapid fabrication of porous carbon nanofibers - Haoyue Zhao; Xinyu Li; Fangqin Su; Ning Qi; Jian Fang (Materials & Design)
High-temperature heat treatment is a crucial thermochemical process for pyrolysis/carbonization of carbon nanofibers (CNFs). However, the inefficient heat transfer process of traditional heating methods often results in inhomogeneous heating, low porosity, long preparation times, and high energy consumption. Here, we first use electrospinning and microwave heating techniques to rapidly fabricate porous CNFs with the help of microwave absorbers. To deeply understand the microwave heating mechanism and differences with traditional heating, we systematically investigate and analyze the effects of the type and concentration of the microwave absorbers, microwave heating parameters, and two heating mechanisms (microwave and traditional heating) on the fabrication of CNFs by experimental investigation and COMSOL simulations. Such microwave heating technique can enable an ultrafast heating rate (up to 250 °C min−1 on average). Due to the rapid internal and volumetric heating, CNFs prepared using microwave heating exhibit a larger carbon content (92.86 %) and a larger BET specific surface area (687 m2/g) than their counterparts prepared using traditional heating methods (88.49 % and 460.7 m2/g). Moreover, the possible mechanisms of microwave heating have been explained. ​This work paves the way for the fabrication of porous CNFs and other advanced carbon nanomaterials using microwave heating techniques.